2015
DOI: 10.1017/s0022215115000602
|View full text |Cite
|
Sign up to set email alerts
|

Bone-anchored hearing aids and unilateral sensorineural hearing loss: why do patients reject them?

Abstract: The uptake rate was 30 per cent for audiologically suitable patients. Almost half of suitable patients did not perceive a sufficient benefit to proceed to device implantation and a significant proportion rejected it. It is therefore important that clinicians do not to rush to implant all unilateral sensorineural hearing loss patients with a bone-anchored hearing aid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 18 publications
3
18
0
Order By: Relevance
“…Whether or not SSD listeners opt for a CROS intervention might depend on several factors. Perceived limited benefits after a soft-band trial is one of the common reasons to decline implantation (Saroul et al, 2014; Siau et al, 2015). Alternatively, it might be that (congenital) SSD patients are not aware of the disadvantages of unilateral hearing (Lieu, 2004, 2013; Vila and Lieu, 2015), and therefore do not ask for clinical help.…”
Section: Introductionmentioning
confidence: 99%
“…Whether or not SSD listeners opt for a CROS intervention might depend on several factors. Perceived limited benefits after a soft-band trial is one of the common reasons to decline implantation (Saroul et al, 2014; Siau et al, 2015). Alternatively, it might be that (congenital) SSD patients are not aware of the disadvantages of unilateral hearing (Lieu, 2004, 2013; Vila and Lieu, 2015), and therefore do not ask for clinical help.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, measuring quality of life and wellbeing using the concept of capabilities has gained more interest [6]. It can be expected that interventions that entail placing a percutaneous implant to improve hearing, may influence an individual in more ways than just solely altering hearing (e.g., the ability to participate in society versus the perceived disadvantages of these types of implants such as cosmetic and social concerns [7, 8]). This perspective will be considered in this trial as well.…”
Section: Introductionmentioning
confidence: 99%
“…Comparison data are available for other BCHDs. It was reported that 4.5% of one clinics 602 BCHD caseload required device removal [ 16 ]; 2% due to pain, 1.2% due to infection, and the remaining due to a variety of other reasons. To conduct a comparative review of outcome with sufficient cases for the VSB and BB a multi-site study is required to overcome the relatively small number of implantations at individual sites.…”
Section: Introductionmentioning
confidence: 99%